Análisis financieros de los activos y pasivos de la Empresa Comercial JAPÓN – Sucursal Ventanas - Barros Vizcaino, Bielka Valkyria (2021)
This case study was carried out at the Japan Warehouse - Ventanas Branch, in order to analyze its financial statements to generate an interpretation of the financial situation of the company's assets and liabilities. The quantitative research methodology was used, which allowed the application of financial indicators, facilitating the comparison of results between business periods to generate the corresponding accounting and financial analysis. A financial literature review was carried out to argue the interpretation of the data obtained and raised in the case. In addition, an interview was used with the head of the branch to obtain information associated with the current administrative and financial situation of said organization. The results obtained were as follows: high level of accounts receivable portfolio, low level of cash, majority dependence on current assets to generate income, low indebtedness, sufficient resources to cover liabilities, decrease in sales income from 2018 to 2018 2019, sales costs represent 65% to 70% of total income, low level of expenses compared to its income, among others.